2017
DOI: 10.1097/ta.0000000000001486
|View full text |Cite
|
Sign up to set email alerts
|

The impact of patient weight on burn resuscitation

Abstract: Therapeutic/care management, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…The present study showed the Body Mass Index (BMI) mean indicate as a preobese stage. The present finding is merly in agreement with (Liu et al, [8] ) who carried out a study entitilled as "the impact of patient weight on burn resuscitation" and found that the mean BMI was in the preobese stage. "From the investigator point of view".…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study showed the Body Mass Index (BMI) mean indicate as a preobese stage. The present finding is merly in agreement with (Liu et al, [8] ) who carried out a study entitilled as "the impact of patient weight on burn resuscitation" and found that the mean BMI was in the preobese stage. "From the investigator point of view".…”
Section: Discussionsupporting
confidence: 93%
“…The current study demonstrated a significant statistical difference in Body Mass Index (BMI) category in relation to patient's status. In the same line (Liu, et al, [8] ) conducted a study titiled as" The impact of patient weight on burn resuscitation" and reported that there is a significant statistical relationship between total sample, obese, and nonobese burned patients. On the other hand, (Tsurumi, et al, [11] ) who conducted a study about "do standard burn mortality formulae work on a population of severely burned children and adults?"…”
Section: Discussionmentioning
confidence: 99%
“…Considering the filter mechanism within the process of stepwise multiple linear regression, we believe such results indicated that these variables were statistically relevant to TCC solitarily according to correlation analysis or simple linear regression, but only tracheotomy had a significant effect on TCC in this patient set. Inhalation injuries have been involved in previous burns fluid research, but most of these studies showed imbalance a higher volume in each target group with a higher incidence of inhalational injury, 8,11 and most other research studies excluded patients with inhalation injuries. Moreover, to our knowledge, it was not stated whether inhalational injury had been taken into account for the determination of the resuscitation volume.…”
Section: Discussionmentioning
confidence: 99%
“…4,9,10 There has been sporadic research on other factors that influence fluid volume calculation, including inhalational injury, mechanical ventilation, and obesity, although there has been no consensus in terms of findings. 8,11,12 Furthermore, questions regarding whether different depths of burn injury should be treated differently when calculating the fluid volume has drawn attention, resulting in opposing perspectives. 13,14 Meanwhile, methods that treat full-thickness burn area (FTBA) and partial-thickness burn area (PTBA) differently, such as the Burn Index, have long been used.…”
Section: Introductionmentioning
confidence: 99%
“…For adult patients between 40 and 130 kg, this reliably produces an initial rate that falls within the Brooke and Parkland recommendations [39][40][41]. Many attempts have been made to improve upon existing equations by incorporating additional variables and calculations with the goal of accurately predicting ongoing fluid needs [42][43][44][45][46]. The Rule of Ten, however, was developed in response to calls for a simplified burn resuscitation formula that emphasizes the importance of precise titration over complex equations, minimizes recall and calculation errors, and is rapidly implemented during an emergency without delaying care [4,32,[47][48][49].…”
Section: Resuscitation Calculationsmentioning
confidence: 99%